Optimization of Sensor Grid aided by Modelling of Sensor Relationships with Digital Filters - Gorecki, J.; Miedzinski, B. (Elektronika ir Elektrotechnika, 2011)
The paper discusses optimization method based on the coverage probability. Presented optimization method can be applied both in the symmetrical sensor grids and asymmetrical sensor grids where sensors are not distributed uniformly. It is revealed that applying post-processing calculations like linear-regression makes incredible improvement in the optimization process. However despite of good correlation between particular sensors, there is a significant risk that causal connection between correlating and correlated sensor does not exist. This paper describes how to detect causal dependency. Ill. 2, bibl. 5, tabl. 2 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.283